(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
INTRODUCTION:Management of airway is one of the primary responsibilities of anesthesiologist1. Supraglottic airway devices have become a standard fixture in airway management, filling a niche between the face mask and tracheal tube in terms of both anatomical position and degree of invasiveness. They have separate gastric channel to reduce regurgitation & pulmonary aspiration2.Proseal LMA has unique double cuff arrangement, main cuff is inflated to seal the laryngeal opening and additional pharyngeal cuff helps to improve the airway seal which make the PLMA ideal for positive pressure ventilation. ‘I-gel’ is a non-inflatable supraglottic airway device designed to avoid compression trauma.Objectives of the study were Quality of insertion, Complications during insertion, Quality of airway sealing, Analysis of hemodynamic parameters, Post operative complications.METHODS: Total 60 patients were divided in 2 groups: A & B. Airway secured with I-gel & PLMA respectively.Ease of insertion of devices, airway sealing quality score, ease & number of attempts of gastric tube insertion were noted. RESULTS: I-gel is better than PLMA in term of faster & easy insertion requiring less manipulation with low incidence of complications during insertion, less hemodynamic stress response and lower postoperative complications. CONCLUSION: Among the second generation supraglottic airway device I-gel is a better & safe alternative to PLMA during elective surgeries.